Cholangiocarcinoma among offset colour proof-printing workers exposed to 1, 2-dichloropropane and/or dichloromethane. Issue 7 (14th March 2013) - Kumagai, Shinji; Kurumatani, Norio; Arimoto, Akira; Ichihara, Gaku
Abstract : Objectives: The present study was conducted to investigate the relationship between occupational chemical exposure and incidence of cholangiocarcinoma among workers in the offset colour proof-printing section of a small printing company in Osaka, Japan. Methods: We identified 51 men who had worked in the proof-printing room, and 11 men who had worked in the front room for at least 1 year between 1991 and 2006. We interviewed them about the chemicals they used, and estimated their levels of exposure to chemicals. We also investigated the medical records of 11 cholangiocarcinoma patients, and calculated the standardised mortality ratio (SMR) from 1991 to 2011. Results: Workers used 1, 2-dichloropropane (1, 2-DCP) from approximately 1985 to 2006, and dichloromethane (DCM) from approximately 1985 to 1997/1998. Exposure concentrations were estimated to be 100–670 ppm for 1, 2-DCP and 80–540 ppm for DCM among the proof-printing workers. All 11 patients were pathologically diagnosed with cholangiocarcinoma. Ages at diagnosis were 25–45 years, and ages at death were 27–46 years among the six deceased individuals. The primary cancer site was the intrahepatic bile duct for five patients, and the extrahepatic bile ducts for six. All patients were exposed to 1, 2-DCP for 7–17 years and diagnosed with cholangiocarcinoma 7–20 years after their first exposure. Ten patients were also exposed to DCM for 1–13 years. The SMR for cholangiocarcinoma was 2900 (expected deaths: 0.00204, 95% CI 1100 to 6400) for all workers combined. Conclusions: These findings suggest that 1, 2-DCP and/or DCM may cause cholangiocarcinoma in humans.